Respuesta :

Answer: y = -2/3(x-3)^2 + 0 or y = -2/3(x-3)^2

Step-by-step explanation:

vertex form is y=a(x-h)^2 + k

here we can see the vertex is (3,0) which is (x,y). Or (h,k) in this case.

so to plug that into vertex form, we now have y=a(x-3)^2 + 0. or just y=a(x-3)^2.

now we need to find "a" which is the leading coefficient. to do that we can plug in the (6,-6) for the x and y parts of the above equation. so we'd have

-6=a(6-3)^2. which goes to -6=a(2)^2 which is -6=4a. divide each side by 4 to get a = -2/3. plug this in for a

the final equation would be y = -2/3(x-3)^2 + 0 or y = -2/3(x-3)^2

ACCESS MORE